2021
DOI: 10.1097/inf.0000000000003389
|View full text |Cite
|
Sign up to set email alerts
|

Population-based Incidence of Myopericarditis After COVID-19 Vaccination in Danish Adolescents

Abstract: The impact of a designated cardiology team involving telemedicine home monitoring on the care of children with single-ventricle physiology after norwood palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 7 publications
5
48
0
Order By: Relevance
“…The clinical phenotype in the only individual in our cohort with MIS-C after breakthrough infection was similar to the phenotype in unvaccinated individuals, but was remarkable due to presentation with severe chest pain, which is rarely seen in unvaccinated children with MIS-C, but reported as an rare adverse event to vaccination. 11 Since the patient had completed the Pfizer-BioNTech vaccine 4 months before the development of MIS-C, vaccine-induced MIS-C was less plausible, despite severe chest pain being reported as the presenting symptom in vaccine-induced MIS-C. 16 The other cases of MIS-C reported after breakthrough infection in vaccinated individuals had a similar phenotype as in non-vaccinated children, with hypotension and several organs involved, but not severe chest pain as the initial presentation. 6,21 The estimation of the incidence of MIS-C is dependent on a precise number of MIS-C cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical phenotype in the only individual in our cohort with MIS-C after breakthrough infection was similar to the phenotype in unvaccinated individuals, but was remarkable due to presentation with severe chest pain, which is rarely seen in unvaccinated children with MIS-C, but reported as an rare adverse event to vaccination. 11 Since the patient had completed the Pfizer-BioNTech vaccine 4 months before the development of MIS-C, vaccine-induced MIS-C was less plausible, despite severe chest pain being reported as the presenting symptom in vaccine-induced MIS-C. 16 The other cases of MIS-C reported after breakthrough infection in vaccinated individuals had a similar phenotype as in non-vaccinated children, with hypotension and several organs involved, but not severe chest pain as the initial presentation. 6,21 The estimation of the incidence of MIS-C is dependent on a precise number of MIS-C cases.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the paediatric nationwide COVID-19 research project, all 18 departments had a principal investigator responsible for prospective realtime data collection to REDCap, a secure web application, including details on clinical characteristics, treatment, and outcome of patients with COVID-19-associated disease, including MIS-C, since March 12, 2020. 3,10,11 To ensure completeness of MIS-C cases identified by the prospective data collection, patients hospitalised with ICD-10 diagnosis codes for MIS-C (DB972B and DB972B1) were obtained through the Danish National Patient Registry. 12 We matched cases from the prospective realtime data collection and those identified through ICD-10 diagnosis codes through the unique social security number for each person in Denmark.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no reports of myocarditis and pericarditis in our study, but this did not mean that myocarditis or pericarditis was not worthy of attention. According to the survey, 350 cases of myocarditis occurred among 8.9 million adolescents who have been vaccinated with BNT162b2 vaccine in the United States [ 14 ]; there were 97 males and 16 females with pericarditis, and myocarditis occurred in every million 12–17 year-old adolescents vaccinated with BNT162b2 vaccine in Denmark [ 30 ]. It reminded us that it was still necessary to monitor and follow up serious adverse events in children and adolescents vaccinated with SARS-CoV-2 vaccines, especially adverse events, such as pericarditis, myocarditis, and allergic purpura.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of myocarditis was five times higher in the 16–30-year-old group (1/20,000) compared to that in the general population (1/100,000) vaccinated with the same vaccine [ 33 , 34 ]. In Danish adolescents, the incidence of myopericarditis after BNT162b2 vaccination was revealed as 97 males and 16 females per million among individuals 12–17 years of age [ 35 ]. The present study similarly found that the risk of myocarditis following the BNT162b2 vaccination among adolescents (12–17 years old) was significantly higher in males than in females.…”
Section: Discussionmentioning
confidence: 99%